Penyuluhan Tentang Penyakit Kecacingan pada Anak Stunting di Posyandu Desa Bone Kecamatan Nekamese Kabupaten Kupang Nusa Tenggara Timur Tahun 2024 - Meliance Bria; Ni Made Susilawati (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
Stunting is a chronic nutritional problem in children that can occur from the womb to the beginning of a baby's life until they are two years old. Worms are an infectious disease caused by the STH (Soil Transmitted Helminths) worm parasite. The impact of worms on children is that it results in a decline in health and nutrition. One of the activities carried out is socialization about worm disease in stunted children as an effort to increase public awareness from an early age through monitoring children's growth and development at posyandu. The aim of PkM is to increase the knowledge of mothers of toddlers about preventing and treating stunting and worms. The method used is counseling through health education on how to prevent and treat worms early in stunted children. The PkM target is 28 mothers of toddlers. The implementation was carried out in Bone Village. The results of the outreach show that the education and knowledge of mothers of toddlers is still low so that the implementation of socialization activities can increase knowledge and build commitment among mothers with toddlers in the Bone Village area to monitor the nutritional status and growth and development of toddlers against worms at the Posyandu.